Growth parameters and maximum age of prawn, Penaeus semisulcatus (De Haan) in Bushehr waters, Persian Gulf - Niamaimandi, Nassir; Arshad, Aziz; Daud, Siti Khalijah; Saad, Che Roos; Kiabi, Bahram (Iranian Fisheries Science Research Institute, 2008)
Carapace length frequency data of green tiger prawn, Penaeus semisulcatus, were monthly collected from 50 stations along the coastal waters of Bushehr, Persian Gulf, during January 2003 to March2004. FiSAT program was used to analyse a total of 535 shrimps including292 females and 243 males, for the relationships of total length, weight and carapace length. The L∞ and K for males were estimated at 38mm CL and 1.6 year-1 and for the females were 50.40mmCL and 2.20 year-1, respectively. Maximum age (Tmax) was 20 months for the males and 15 months for the females. The growth of the shrimp was found to be rapid during summer and autumn and negligible during winter and spring.